2023
DOI: 10.3389/fcell.2023.1143844
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the foxe1 gene in zebrafish reveals conserved functions in development of the craniofacial skeleton and the thyroid

Abstract: Introduction: Mutations in the FOXE1 gene are implicated in cleft palate and thyroid dysgenesis in humans.Methods: To investigate whether zebrafish could provide meaningful insights into the etiology of developmental defects in humans related to FOXE1, we generated a zebrafish mutant that has a disruption in the nuclear localization signal in the foxe1 gene, thereby restraining nuclear access of the transcription factor. We characterized skeletal development and thyroidogenesis in these mutants, focusing on em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…In our earlier study, we found FOXE1 in the thyroid follicles of developing zebrafish, which further bolstered the relation between FOXE1 and thyroid metabolism (Raterman et al 2023). In that study we found no differences in the number of thyroid follicles between mutants and wild type larval fish.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…In our earlier study, we found FOXE1 in the thyroid follicles of developing zebrafish, which further bolstered the relation between FOXE1 and thyroid metabolism (Raterman et al 2023). In that study we found no differences in the number of thyroid follicles between mutants and wild type larval fish.…”
Section: Discussionsupporting
confidence: 59%
“…In mammals, hypothyroidism leads to delayed endochondral ossification, impaired growth, and reduced mineralization (Devdhar, Ousman, and Burman 2007; Bassett and Williams 2016; Persani 2012). Previously we reported that skeletal mineralization during endochondral ossification is decreased in foxe1 mutant larvae (Raterman et al 2023), but at that time we could not relate this to hypothyroidism yet. We now assessed a reduced mineralization and an increased osteoclast activity in scales from foxe1 and dio2 zebrafish mutants which we link to hypothyroidism.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations